Crystallization of the CHAP domain of the endolysin from Staphylococcus aureus bacteriophage K. Issue 12 (1st December 2013) - Sanz‐Gaitero, Marta; Keary, Ruth; Garcia‐Doval, Carmela; Coffey, Aidan; van Raaij, Mark J.
<x xml:space="preserve">Abstract</x> CHAPK is the N‐terminal cysteine, histidine‐dependent amidohydrolase/peptidase domain (CHAP domain) of the Staphylococcus aureus bacteriophage K endolysin LysK. It is formed from the first 165 residues of LysK and functions by cleaving specific peptidoglycan peptide bonds, causing bacterial lysis. CHAPK can lyse S. aureus when applied exogenously, making it a good candidate for the treatment of multidrug‐resistant Staphylococcus aureus infections. Here, the crystallization of CHAPK and the collection of native and derivative data to high resolution, which allowed structure solution, are reported. The structure may help to elucidate the mechanism of action and in the design of chimeric proteins or mutants with improved antibacterial activity.